Full spectrum of vitamin D immunomodulation in multiple sclerosis: mechanisms and therapeutic implications. Issue 4 (30th June 2022) - Galoppin, Manon; Kari, Saniya; Soldati, Sasha; Pal, Arindam; Rival, Manon; Engelhardt, Britta; Astier, Anne; Thouvenot, Eric
Abstract: Vitamin D deficiency has been associated with the risk of multiple sclerosis, disease activity and progression. Results from in vitro experiments, animal models and analysis of human samples from randomized controlled trials provide comprehensive data illustrating the pleiotropic actions of Vitamin D on the immune system. They globally result in immunomodulation by decreasing differentiation of effector T and B cells while promoting regulatory subsets. Vitamin D also modulates innate immune cells such as macrophages, monocytes and dendritic cells, and acts at the level of the blood–brain barrier reducing immune cell trafficking. Vitamin D exerts additional activity within the central nervous system reducing microglial and astrocytic activation. The immunomodulatory role of Vitamin D detected in animal models of multiple sclerosis has suggested its potential therapeutic use for treating multiple sclerosis. In this review, we focus on recent published data describing the biological effects of Vitamin D in animal models of multiple sclerosis on immune cells, blood–brain barrier function, activation of glial cells and its potential neuroprotective effects. Based on the current knowledge, we also discuss optimization of therapeutic interventions with Vitamin D in patients with multiple sclerosis, as well as new technologies allowing in-depth analysis of immune cell regulations by vitamin D. Abstract : Galoppin et al . provide a comprehensive analysis of the biological effects of Vitamin D (VitD) in animal models and patients with multiple sclerosis, especially focusing on regulation of immune cells, blood–brain barrier function, activation of glial cells and therapeutic trials. They discuss optimization of therapeutic interventions with VitD in multiple sclerosis. Graphical Abstract: Graphical Abstract